Green Logistics Adoption among 3PL Companies - Rozelin Abdullah; Mat Daud; F. Ahmad; A. Shukti (International Journal of Supply Chain Management, 2016)
Logistics is one of the causal factors of environment pollution through its activities. Previous studies had shown Green initiatives adoption by Third Party Logistics (3PL) companies may reduce environment impact. These companies are the stakeholders of logistics activities and supply chain management. The aim of the research is to discover the involvement of Third Party Logistics (3PL) companies in applying Green Logistics initiatives in the event of rendering logistics services to its customers. The parameter of this study is within the scope of 3PL companies already adopted Green Logistics practices in Malaysia. The paradigm of green logistics implementation in this study within three domains which are the customers, the logistics operations and the logistics amenities. This will identify the positive and negative impacts of adopting Green initiatives experienced by the 3PL logistics companies in satisfying its customers requirement. There are several evidence to support these adoptions through previous studies especially on the influence of Environment Management System (EMS) and Green Supply Chain Management (GSCM) practices by manufacturing companies. This paper focus on the adoption of Green Logistics initiatives by Third Party Logistics (3PL) companies in Malaysia via case study research methodology.